Recent advances microRNAs and metabolic reprogramming in colorectal cancer research - Xiong, Bin; Huang, Qiaoyi; Zheng, Huida; Lin, Shu; Xu, Jianhua (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is one of the cancers with the highest incidence and mortality. Alteration of gene expression is the main pathophysiological mechanism of CRC, which results in disturbed signaling pathways and cellular metabolic processes. MicroRNAs take a part in almost all pathophysiological processes and are correlative with colorectal cancer metabolism, proliferation, and chemotherapy resistance. Metabolic reprogramming, one of the important features of cancer, is closely correlative with the development and prognosis of cancers, including colorectal cancer. MicroRNAs can target enzymes involved in metabolic processes, thus playing a regulatory role in tumor metabolism. The disorder of signaling pathway is another characteristic of tumor, which induces the occurrence and proliferation of tumor, and is closely correlative with the prognosis and chemotherapy resistance of tumor patients. MicroRNAs can target on the components of the signaling pathways to regulate the transduction of the signaling pathways. Comprehending the function of microRNAs in the occurrence and proliferation of CRC, helps us to understand the characteristics of the treatment, prognosis and chemotherapy resistance of colorectal cancer. This article reviews the relationship between colorectal cancer and microRNA expression, and provides strategies for exploring potential options for colorectal cancer treatment.